Design thinking and collaborative governance for public service innovation an application in civic technology - Millan, Sharon B.
One avenue for innovation creation in public services is collaboration. This study set out to determine whether deliberate collaboration between government, citizen and IT practitioners using a design thinking protocol can be an intervention for creating public service innovations in the form of civic technologies. This study looked into the interaction dynamics that depict communication patterns of idea generation, knowledge sharing, sustained idea expression, sustained disagreement and even blocking between government. citizen and IT practitioner participants and how these interactions led to public service innovation design prototypes. These prototypes were then tested in terms of their usability. The collaborators were observed to have engaged in problem articulation. abductive reasoning, divergent thinking, prototyping and validating. This resulted in working clickable city mobile app prototypes that received almost wide acceptance during the usability tests.